Hotline student's book : - Hutchinson, Tom (Oxford University Press, 1986)
The "Hotline" English programme has been designed as a four-year course for secondary students, taking them from beginner to intermediate level. Distinguishing features of this programme include the contemporary use of language, project work which practices all four learning skills, constant revision, photostories, a learning diary and a pronunciation guide at the back of each text. The course features a student's book, a teacher's guide, a workbook and a cassette at every level. The workbook includes cross-cultural activities, which invite comparisons between the student's own culture and foreign cultures, in order to develop an awareness of cultural differences and similarities. There is also a self-assessment check in each workbook, which gives learners the opportunity to reflect on parts of the text which were useful, difficult or interesting, and allows them to assess their own progress.